2010
DOI: 10.1364/oe.18.00a237
|View full text |Cite
|
Sign up to set email alerts
|

Light trapping in ultrathin plasmonic solar cells

Abstract: Abstract:We report on the design, fabrication, and measurement of ultrathin film a-Si:H solar cells with nanostructured plasmonic back contacts, which demonstrate enhanced short circuit current densities compared to cells having flat or randomly textured back contacts. The primary photocurrent enhancement occurs in the spectral range from 550 nm to 800 nm. We use angle-resolved photocurrent spectroscopy to confirm that the enhanced absorption is due to coupling to guided modes supported by the cell. Full-field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
484
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 610 publications
(494 citation statements)
references
References 35 publications
9
484
0
1
Order By: Relevance
“…Significant attention has been devoted to the optimization of the metal nanostructure size and shape 2,[20][21][22][23][24] . It was found that relatively large (50-150 nm) metallic particles are desirable because they exhibit relatively little absorption losses due to a favourable ratio of the scattering to absorption cross section.…”
Section: Resultsmentioning
confidence: 99%
“…Significant attention has been devoted to the optimization of the metal nanostructure size and shape 2,[20][21][22][23][24] . It was found that relatively large (50-150 nm) metallic particles are desirable because they exhibit relatively little absorption losses due to a favourable ratio of the scattering to absorption cross section.…”
Section: Resultsmentioning
confidence: 99%
“…With properly engineered photonic nanostructures, sunlight can be trapped within the thin absorbing silicon layers, thereby enhancing light absorption and thus conversion efficiencies. Recently, exciting new strategies for improving light harvesting have gained tremendous interest, including nanopillar-and nanohole-type geometries, [1][2][3][4][5][6] plasmonics and guided modes, [7][8][9][10][11][12] and photonic crystals. [13][14][15] Light scattering at nanotextured interfaces provides a powerful and proven alternative to improve the optical performance of thinfilm silicon devices.…”
mentioning
confidence: 99%
“…Till date, a number of structures have been used that are capable of coupling the incident light to surface modes such as surface plasmon polaritons (SPPs) and localized surface plasmons (LSPs), and different photonic modes so that light can be confined in a sub-wavelength dimensional structure. The structures mainly use nano-structures and gratings of metal and dielectric material in different layers of solar cells [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%